USING OF DERIVATE- GRAPHICAL ANALYSIS FOR INVESTIGATION OF EFFICIENCY OF EXOTHERMAL REACTIONS IN THE PROCESSES OF PROFITABLE FEEDING OF CASTING - D. M. Kukuj; Ju. N. Fasevich; V. V. Shevchuk; A. I. Turok (Литьë и металлургия)
It is determined that derivate-graphic analysis gives possibility to investigate efficiency of exothermal reactions in the process of profitable feeding of castings.